PERLINDUNGAN KONSUMEN ATAS KERUSAKAN DAN KEHILANGAN BAGASI PENUMPANG PESAWAT UDARA OLEH MASKAPAI PENERBANGAN (STUDY KASUS PT. METRO BATAVIA CABANG MEDAN) - FREDDY LUTH PUTRA PURBA; T KEIZERINA DEVI; WINDHA WINDHA (TRANSPARENCY, 2013)
With the development of more advanced era, directly influenced the development of technology anyway. All flights include different routes, and has become a much-needed public transport today. In this paper I discuss specifically to passenger baggage loss and baggage whether cabin or baggage. Where this is a common problem and is experienced at present which is of course detrimental to passengers using air transport. To ensure passenger rights or the rights of consumers are harmed by the carrier it should be the responsibility of the carrier so that the carrier more secure rights that exist on the consumer or passenger. The problem in this paper is how the legal protection of consumers or the passenger for damages and loss that occurs in baggage, either baggage or cabin baggage and the airline liability form (Batavia Airlines) as a scheduled commercial carrier transportation of national. The data obtained by the primary data obtained through regulations set by the authorities and data from private air transport companies Batavia Airlines. The results of the study explained that in Indonesian positive law, there are regulations governing the legal protection of passenger air transport, namely Law No. 1 Year 2009 About Flights Ministerial Regulation No. 77 Year 2011 About Air Transport Carrier Liability, Ordonasi Air Freight 1939, as well as from the Batavia Airlines other than follow the rules that have been enacted, they have their own way in carrying out the responsibility for damage caused to the passengers. Kata Kunci: Perlindungan Konsumen, Tanggungjawab Pengangkut, Pengangkutan Bagasi.